2023
DOI: 10.1002/anie.202300088
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐responsive Single‐Molecule Magnet Showing 0D to 1D Single‐Crystal‐to‐Single‐Crystal Structural Transition and Hysteresis Modulation

Abstract: Photo‐responsive lanthanide‐based single‐molecule magnets (SMM) hold great promise for future switching and memory devices. Herein, we report a dysprosium phosphonate [DyIII(SCN)2(NO3)(depma)2(4‐hpy)2] (1Dy), which features a supramolecular framework containing layers of hydrogen‐bonding network and pillars of π–π interacted anthracene units. The photocycloaddition reaction of anthracene pairs led to a rapid and reversible single‐crystal‐to‐single‐crystal (SC–SC) structural transition to form the 1D coordinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Generally, the application of small dc fields during the ac measurements can eliminate the QTM and induce the happening of slow magnetic relaxation. Additionally, a 1 kOe dc field was the most used optimum field for the suppression of QTM, especially for cobalt complexes. , For compounds 1 and 2 , temperature- and frequency-dependent ac susceptibility signals were observed when the 1 kOe dc field was applied (Figure , Figure S8, SI). These results support two SIM-CPs of compounds 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the application of small dc fields during the ac measurements can eliminate the QTM and induce the happening of slow magnetic relaxation. Additionally, a 1 kOe dc field was the most used optimum field for the suppression of QTM, especially for cobalt complexes. , For compounds 1 and 2 , temperature- and frequency-dependent ac susceptibility signals were observed when the 1 kOe dc field was applied (Figure , Figure S8, SI). These results support two SIM-CPs of compounds 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Besides the mononuclear complexes, a series of coordination polymers (CPs) or metal–organic frameworks (MOFs), which are built with metal nodes (a single metal ion or a cluster) and organic linking ligands were reported to display slow relaxation of the magnetization under zero filed or applied dc fields. Such 3d or 4f complexes can be considered as SIM-CPs or SMM-CPs because magnetically they exhibit the nature of their metal nodes due to negligible internode interactions. In fact, they have provided a new platform for manipulating the magnetic dynamics. As an illustrative example, Cano et al reported the guest-dependent SIM behavior in a family of cobalt­(II) MOFs .…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state dielectric switches have attracted much attention for their property of reversible conversion of their own states by external stimuli, such as temperature, light, and force, and as one of their important constituents, [1][2][3][4][5][6] OIHMs have made rapid development in the past decade. [7][8][9][10][11][12][13][14][15] In particular, ferroelectric and ferroelastic materials, whose structural flexibility provides innate facilities for improving the optical and electrical properties of the underlying crystalline materials of the devices, possess enormous potential and a wide range of applications in energy conversion, information conversion, and storage. [16][17][18][19][20] Molecular ferroelastics are more advantageous than conventional inorganic dielectrics in terms of environmental friendliness, mechanical flexibility, low acoustic impedance, and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] The blocking temperature T B , being the temperature below which magnetisation is retained, would be the most sensible parameter for determining SMM performance. However, the exact definition of T B often varies between groups with the more commonly utilised definitions being; the maximum temperature at which magnetic hysteresis is observed, 8,9 (the temperature corresponding to the maximum zero-field AC susceptibility), [10][11][12][13] and the temperature at which the relaxation time is equal to 100 seconds. [14][15][16] Furthermore, the exact definition used for T B is not always present in publications, making comparisons of T B between studies difficult.…”
Section: Introductionmentioning
confidence: 99%